KOMPETENSI PENDIDIK PERSPEKTIF AL-QUR’AN DALAM MEMBANGUN PROFESIONALITAS PADA ERA SOCIETY 5.0 - Fitriani; Karman (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
This study aims to discuss the competence of educators from the perspective of the Koran in building professionalism in the Era of Society 5.0. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the Koran, while the material object is verses about educator competence. The results and discussion of this study indicate that the competencies that must be possessed by an al-Qur'an perspective include 1) personal-religious competence; 2) socio-religious competence; 3) professional-religious competence; 4) physical-religious competence. This study concludes that the competence of educators in the Qur'an must become a part of an educator, because the competence of an educator determines the achievement of the educational and learning process. Keywords: Al-Qur'an, Educator Competence, Era of Society 5.0